الكفاءة الاقتصادية لمزارع تسمين العجول في محافظة حمص. - يعقوب غسان; عباس حسان; الــــنمر فاتـــــن (Latakia University Journal -Biological Sciences Series, 2016)
This study aimed to evaluate and study the economic efficiency of farms fattening calves in Homs, during the period 2008-2013 in both the public sector ( farm Homs ) and cooperative ( private farms licensed for fattening calves ), where the study was conducted on the relevant section fattening calves at a farm Homs , also conducted on a sample of the cooperative sector farms includes 19 farm . The average number of calves where about 20 head of Friesian ,through cost and revenue account , and using some of the economic indicators . The results showedthat the averagerevenuebefore the crisiswas about6272SPforfarmHoms, about 17829.1SPfor thefarmescooperative sector, andduring the crisisamounted to15676.3SPatthefarmof Homs, about 53931.3SPwith thecooperative sectorfarms, while the averagecost ofproductionamounted to1kgof the gross weightof the animalbefore the crisisabout199.9SPforfarmHoms, and about176.3SPfor thefarmercooperative sector, andduring the crisisamounted to about505.2SPfarmatHoms, andatabout459.6SPfarmscooperative sector, asthe averageannualnet profitbeforethe crisisabout10570.8SPforfarmHoms, about 34573.8SPfor thefarmescooperative sector, andduring the crisiswas about29757.1SPfarmatHoms, and about129634.8SPfarmswith thecooperative sector. The averagenet profit marginstoodbefore the crisisabout 14% for farmHoms, and about16.1% for thefarmescooperative sector, andduring the crisisamounted to about15.8% for theSPfarmHoms, and about20.2% in the cooperative sectorFarms.The averageyieldper unitspendingbefore the crisisabout 1.6SP/ unitspendingforfarmHoms, and about1.19SP/ unitspendingforatthe cooperative sectorfarms, andduring the crisiswas about1.2SP/ unitspendingforfarmHoms, and aboutSP1.3/ unitto spendwiththe cooperative sectorfarms. The averageprofitabilitycoefficientrelativetoinvested capitalbefore the crisisabout11.3% for farmHoms, and about18.8% in the cooperative sectorfarms, andduring the crisisamounted to about17.1% SPfarmHoms, and about24.9% in the cooperative sectorfarms. As Averageprofitabilitycoefficientcomparedtothe cost ofproductionhas reachedpre-crisisabout 16.3% for farmHoms, and about19.2% for thefarmercooperative sector, andduring the crisisamounted to about18.8% for theSPfarmHoms, andabout 25.3% in the cooperative sectorfarms. As for thetime ofthe restoration ofthe invested capitalforfarmHoms, it is 6.2 years before the crisis, and 5.3years during the crisis, eitherwith thecooperative sectorfarmsaveragereachedinvested capitalrestorationtimebefore the crisisabout 5.3years, androsethroughto reachabout 4years. هدفت الدراسة إلى دراسة الكفاءة الاقتصادية لمزارع تسمين العجول في محافظة حمص خلال الفترة 2008-2013، في كلا القطاعين: العام، المتمثل بمبقرة حمص، والتعاوني المتمثل بالمزارع الخاصة المرخصة لتسمين العجول؛ إذْ أجريت الدراسة على القسم المختص بتسمين العجول لدى مبقرة حمص، كما أجريت أيضاً على عينة من مزارع القطاع التعاوني تضم 19 مزرعة، متوسط عدد العجول في المزرعة الواحدة 20،20،18،19،18،20 رأس على التوالي خلال سنوات الدراسة (2008-2013) من الفريزيان، وقد تم حساب التكاليف والإيرادات، وباستخدام بعض المؤشرات الاقتصادية. لقد أظهرت النتائج أن نصيب الرأس خلال شهر من التكاليف الكلية قبل الأزمة بلغ 5391.1ل.س للقطاع العام، و14947.9ل.س للقطاع التعاوني، وبلغ خلال الأزمة13196.5ل.س للقطاع العام، و43128.4 ل.س للقطاع التعاوني، وبلغ نصيب الرأس من الإيرادات قبل الأزمة 6272ل.س وسطياً في مبقرة حمص، و17829.1ل.س وسطياً في مزارع القطاع التعاوني، وخلال الأزمة بلغ 15676.3 ل.س وسطياً في مبقرة حمص، و 53931.3ل.س وسطياً في مزارع القطاع التعاوني ، في حين بلغ نصيب الراس من كلفة إنتاج 1كغ من الوزن القائم للحيوان قبل الأزمة 199.9ل.س في مبقرة حمص، و 176.3 ل.س في مزارع القطاع التعاوني، وخلال الأزمة بلغ 505.2 ل.س في مبقرة حمص، و459.6 ل.س في مزارع القطاع التعاوني، كما بلغ نصيب الراس من الربح السنوي الصافي قبل الأزمة10570.8 ل.س في مبقرة حمص، و34573.8ل.س في مزارع القطاع التعاوني، وخلال الأزمة بلغ 29757.1 ل.س في مبقرة حمص، و129634.8ل.س في مزارع القطاع التعاوني . أما نصيب الراس من متوسط هامش صافي الربح فقد بلغ قبل الأزمة 14% في مبقرة حمص، و 16.1% في مزارع القطاع التعاوني، وخلال الأزمة بلغ 15.8 % ل.س في مبقرة حمص، ونحو20.2% في مزارع القطاع التعاوني . وبلغ نصيب الراس من العائد لكل وحدة إنفاق قبل الأزمة 1.16 ل.س/وحدة إنفاق في مبقرة حمص، و1.19 ل.س/وحدة إنفاق في مزارع القطاع التعاوني، وخلال الأزمة بلغ1.2 ل.س/وحدة إنفاق في مبقرة حمص، و 1.3 ل.س/وحدة انفاق في مزارع القطاع التعاوني. وبلغ نصيب الراس من معامل الربحية بالقياس إلى رأس المال المستثمر قبل الأزمة 11.3% في مبقرة حمص، و18.8 % في مزارع القطاع التعاوني، وخلال الأزمة بلغ17.1 % ل.س في مبقرة حمص، و24.9% في مزارع القطاع التعاوني .أما نصيب الراس من معامل الربحية بالقياس إلى تكاليف الإنتاج فقد بلغ قبل الأزمة 16.3 % في مبقرة حمص، و19.2% في مزارع القطاع التعاوني، وخلال الأزمة بلغ 18.8% ل.س في مبقرة حمص، و25.3% في مزارع القطاع التعاوني. أما بالنسبة إلى زمن استعادة رأس المال المستثمر لدى مبقرة حمص فبلغ قبل الأزمة 6.2سنة، وانخفض خلال الأزمة إلى 5.3سنة، اما بالنسبة إلى مزارع القطاع التعاوني فقد بلغ نصيب الراس من زمن استعادة رأس المال المستثمر قبل الأزمة 5.3سنة ، وارتفع خلالها ليصل 4سنوات.